A Descriptive Study on Risk Factors for Common Non-Communicable Diseases among the Students of a Nursing Training School Attached To a Tertiary Care Hospital of West Bengal - Kamalika Das; Palash Das (Medsci Publications, 2021)
Introduction: Several risk factors would be the predominant cause of non-communicable diseases among the young adolescents girls life style modification maybe the methodology for health promotion & prevention of such non-communicable disease prevalence. Objectives: To identify the several predisposing factors responsible for non-communicable health problems among the young adolescence. Materials & Methods: Sample size was 212 and sampling technique was complete enumeration. A descriptive study was conducted where data analyzed through statistical methods like, chi square test. Result: Study shows majority of the adolescent less than 20yers old and mostly from rural origin and non vegetarian. Most of them had the habit of vegetable & fruit intake though there was no case of addiction but only 56% were habituated with exercise. Conclusion: Unhealthy diet pattern, lack of regular exercise would be the predominant cause of different non-communicable disease pattern where LSM is the best way to rectify the situation.